(untitled) (Avocetta, 2020)
The Barred Warbler Sylvia nisoria is a critically endangered breeding species in Italy, given the severe decline suffered in the last decades and the reduced population size. South Tyrol, an inner Alpine region, is the northernmost Italian breeding area of this warbler, but we lacked recent information about the distribution and population size. In this study, based on surveys carried out in the year 2019 and other recent observations, we assessed a very restricted current distribution of this warbler, and we estimated a population size of 10-30 pairs. We also observed a singing male at unusually high elevation. A comparison of our results to historical data suggests a strong reduction in distribution compared to the 1980s/1990s. The changes in agricultural practices of the last decades might have contributed to determine such decline. Appropriate conservation measures are urgently needed to try to avoid the local extinction of the species.